Faces, Feeling, and Knowledge: Virginia Woolf's The Waves Might Make You Laugh and Cry, but What Does It All Mean?. (27th February 2019) - Harris, Angela
Abstract: Virginia Woolf's The Waves is a difficult novel to comprehend rationally, and yet it is also a very moving novel that can take the reader from ecstasy to despair. This essay explores the epistemological value, if any, of such feelings. If this novel made you cry, would that mean something? Or are your tears merely an emotional response to an aesthetically accomplished work? The Waves explores links between feeling, rational thought, and knowledge. Intense feelings of ecstasy, which cause one to be 'beside oneself' in a positive or a negative sense, are associated with leaps forward in objective knowledge. To explore Woolf's thinking on making meaning, as set out in The Waves, this essay focuses on the faces of Jinny, Neville, and Bernard. The face is a motif almost synonymous with life, which inspires feeling as well as rational (and particularly ethical ) thought. This critical interrogation is made with reference to the new 'positive aesthetics', which also raises questions about the potentialities as well as the limitations of this new literary critical toolbox. Ultimately, this essay asks: given the intense feelings The Waves can inspire, what does The Waves know?